1995
DOI: 10.1016/s0305-7364(05)80002-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed cryopreservation and priming on germination in several cultivars of

Abstract: Seed germination of seven celery cultivars was studied after storage in liquid nitrogen for I or 30 d. Cryopreservation was also carried out on pelleted and primed seeds. None of the treatments applied reduced germination percentages. T 50 (time for germination to reach 50%) significantly decreased in Florida, Utah and Istar cultivars when priming, alone or in combination with cryopreservation, was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Few past studies reported some improvements on T50 (days to reach the full germination level) of the celery seeds, without noticeable reduction in germination percentages, by using cryopreservation technique for conservation or priming pre-treatments with salt solutions of NaNO 3 or KNO 3 or osmopriming [5,6]. Osmopriming with polyethylene glycol 6000 solution for up to 10 days, followed by drying back, substantially lowered mean time germination time of fresh celery seeds, compared to hydropriming [7].…”
Section: Introductionmentioning
confidence: 99%
“…Few past studies reported some improvements on T50 (days to reach the full germination level) of the celery seeds, without noticeable reduction in germination percentages, by using cryopreservation technique for conservation or priming pre-treatments with salt solutions of NaNO 3 or KNO 3 or osmopriming [5,6]. Osmopriming with polyethylene glycol 6000 solution for up to 10 days, followed by drying back, substantially lowered mean time germination time of fresh celery seeds, compared to hydropriming [7].…”
Section: Introductionmentioning
confidence: 99%